Pemantauan Oksigen Otak Dengan Pengukuran Saturasi Oksigen Vena Jugularis (SjvO2) Sebelum Ekstubasi Pada Pasien Cedera Otak Traumatik - Sommeng, Faisal; Arif, Syafri Kamsul (Rumah Sakit Ibnu Sina, Makassar, 2022)
In the group of serious injuries due to traffic accidents, head injury ranks highest, and the discussion of injuries in Indonesia and America is extreme. head injury can cause shock or shock to the brain due to an accident or assault that causes impaired brain function and results in death or death. The main monitoring in the neurointensive care of head injury is the measurement of intracranial pressure (ICP) to combine cerebral perfusion pressure (CPP) and cerebral blood flow (CBF). Moderate to severe brain injury (TBI) will require treatment in an intensive care unit (ICU) with continued monitoring. The primary goal of monitoring is to detect and treat cerebral hypoperfusion for secondary disorders. SjvO2 is a method of monitoring brain perfusion by measuring cerebral venous saturation in the jugular bulb. Monitoring brain perfusion is a guide in managing head injuries, including ventilator weaning and extubation.